2002
DOI: 10.1093/carcin/23.12.2111
|View full text |Cite
|
Sign up to set email alerts
|

Association of p16INK4a and pRb inactivation with immortalization of human cells

Abstract: To examine the association of cell cycle regulatory gene inactivation with human cell immortalization, we determined the expression status of INK4a, Rb, and WAF1/ CIP1, in eleven in vitro immortalized human cell lines, including fibroblasts and keratinocytes. Two human papillomavirus type 16 E6 expressing cell lines with telomerase activity, including a fibroblast cell line and a keratinocyte cell line, expressed no detectable p16(INK4a). These cell lines had a hyperphosphorylated pRb and reduced expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…There is also a growing body of evidence indicating that expression of catalytically active telomerase is insufficient for immortalization of some strains of human fibroblasts. Our previous study, as well as independent investigations, demonstrated that several different stains of fibroblasts expressing hTERT ceased proliferating after a significantly extended lifespan (32)(33)(34)(35). In our study of hTERT-transduced MRC5 lung fibroblasts (MRC5hTERT), growth arrest was not permanent, as subsets of mass cultured cells eventually resumed proliferation, and immortal cell lines were established.…”
mentioning
confidence: 52%
“…There is also a growing body of evidence indicating that expression of catalytically active telomerase is insufficient for immortalization of some strains of human fibroblasts. Our previous study, as well as independent investigations, demonstrated that several different stains of fibroblasts expressing hTERT ceased proliferating after a significantly extended lifespan (32)(33)(34)(35). In our study of hTERT-transduced MRC5 lung fibroblasts (MRC5hTERT), growth arrest was not permanent, as subsets of mass cultured cells eventually resumed proliferation, and immortal cell lines were established.…”
mentioning
confidence: 52%
“…Some authors have noted that hTERT þ cells express a normal cell-cycle arrest and checkpoint protein response to specific challenges including DNA damaging agents (including chromium) (Jiang et al, 1999;Morales et al, 1999;Pritchard et al, 2001;Wood et al, 2001;Gorbunova et al, 2002). In contrast, other authors have reported that there is a loss of p16INK4a and hyperphosphorylation of pRb in hTERT þ cells (Tsutsui et al, 2002;Piboonniyom et al, 2003) and in one cell line a mutation in p53 and abnormal G1 checkpoint (Noble et al, 2004).…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 99%
“…63,64 Conversely, breaking the senescence barrier in order to immortalize cells requires the inactivation of these cell cycle inhibitory genes. 65,66 The latter mechanism likely accounts for the immortalization of AP-1060 cells after ENU mutagenization, since compared to AP-1060S cells, the established line cells showed a marked derepression of genes associated with cell cycle progression and DNA synthesis (Table 3), but with little or no secondary change in telomere length or telomerase activity (Figure 2).…”
Section: Apl Cell Line Ap-1060mentioning
confidence: 99%